2013
DOI: 10.1371/journal.pone.0074889
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Helicoverpa armigera Midgut Digestive Physiology after Ingestion of Pigeon Pea Inducible Leucine Aminopeptidase

Abstract: Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…And NDUFA4 and COX7A, belonging to CYC oxidase (complex IV), could also be able to eliminate ROS by acting as oxygen acceptor to transfer electrons from CYC to O 2 forming H 2 O . Other defense mechanism of cell against apoptosis was the upregulation of ATPase, like ATP5G, to mediate mitochondrial cristae to protect cell from death, and the decreased activities following the consumption of glutathione metabolism‐related proteins (including one leucyl aminopeptidase and four GST) could decrease resistance against xenobiotic compounds and contribute to redox homeostasis . Based on the expression variations after treatment, we suggested that oxidative‐related proteins and glutathione metabolism‐related proteins were regulated to maintain balance of ROS, ATP, pH, and resistance to avoid the mitochondria dysfunction induced by azadirachtin.…”
Section: Discussionmentioning
confidence: 99%
“…And NDUFA4 and COX7A, belonging to CYC oxidase (complex IV), could also be able to eliminate ROS by acting as oxygen acceptor to transfer electrons from CYC to O 2 forming H 2 O . Other defense mechanism of cell against apoptosis was the upregulation of ATPase, like ATP5G, to mediate mitochondrial cristae to protect cell from death, and the decreased activities following the consumption of glutathione metabolism‐related proteins (including one leucyl aminopeptidase and four GST) could decrease resistance against xenobiotic compounds and contribute to redox homeostasis . Based on the expression variations after treatment, we suggested that oxidative‐related proteins and glutathione metabolism‐related proteins were regulated to maintain balance of ROS, ATP, pH, and resistance to avoid the mitochondria dysfunction induced by azadirachtin.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in the digestive system, aminopeptidase serves as a direct defence in the insect midgut and is known to be a crucial enzyme in plant–insect interactions ( Lomate et al 2013 ). In turn, it keeps RPW staying healthy and protected from any hazardous material or substance as a consequence of their feeding habitat.…”
Section: Discussionmentioning
confidence: 99%
“…This group of co-regulated proteins includes proteinase inhibitors (PIs) that disrupt the action of digestive proteases and amino aciddegrading enzymes, including arginase (ARG2) and threonine deaminase (TD2; Figure 1) [50,51]. Leu amino peptidase (e.g., LAP-A) may also participate in this post-ingestive defense system [50,52,53], although a role for LAP-A in wound signaling has also been proposed [54].…”
Section: An Expanding Arsenal Of Gut-active Plant Defense Proteinsmentioning
confidence: 99%